For a twice diffrentiable function f ( x ) , g ( x ) is defined as g ( x ) = ( f ′ ( x ) ) 2 + f ( x ) f ′ ′ ( x ) . For constants a < b < c < d < e , we have ( f ( a ) = 0 , f ( b ) = 2 , f ( c ) = − 1 , f ( d ) = 2 , f ( e ) = 0 .
Find the minimum number of roots of the equation g ( x ) = 0 in ( a , e ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I think, here g(x) is defined on x∈ (a,e). so for g(x) we cannot take x=a or x=e. So the answer must be 5
Log in to reply
Thanks. I have updated the answer to 4.
In future, if you spot any errors with a problem, you can “report” it by selecting "report problem" in the menu. This will notify the problem creator who can fix the issues.
Log in to reply
I think the answer must be 5 . For 3 values of x , f'(x) = 0 and for two values of x ,f(x) = 0.
Log in to reply
@Akash Shukla – I agree that f ( x ) f ′ ( x ) has 5 zeros. The question asks about g ( x ) = [ f ( x ) f ′ ( x ) ] ′ , which then has 4 zeroes.
I now disagree with my previous comments. Looking through this again, the answer is 6. I've edited the solution for clarity to explain why the answer is indeed 6.
Problem Loading...
Note Loading...
Set Loading...
Let h ( x ) = ∫ a x g ( x ) d x = f ( x ) f ′ ( x ) ⇒ h ′ ( x ) = g ( x ) . Then,
h ( x ) = 0 ⇔ f ( x ) = 0 or f ′ ( x ) = 0 .
In the closed interval [ a , e ] , due to the intermediate value theorem , f ( x ) has at least 2 other zeros, so it has 4 zeros in [ a , e ] .
By rolle's theorem , f ′ ( x ) = 0 will have at least 4 − 1 = 3 solutions in ( a , b ) . Thus, h ( x ) will have at least 4 + 3 = 7 solutions in [ a , b ] .
Again by Rolle's theorem , g ( x ) = 0 will have at least 7 − 1 = 6 solutions in ( a , b ) .
To show that this lower bound can be achieved, set f ( x ) = − 1 0 x ( x − 2 ) ( x − 4 ) ( x − 6 ) with 0 = a < b < 2 < c < 4 < d < e = 6 . Then, g ( x ) = ( f ′ ( x ) ) 2 + f ( x ) f ′ ′ ( x ) = [ − 4 0 x 3 + 3 6 0 x 2 − 8 8 0 x + 4 8 0 ] 2 + ( − 1 0 x ) ( x − 2 ) ( x − 4 ) ( x − 6 ) × ( − 1 2 0 x 2 + 7 2 0 x − 8 8 0 ) .
We can manually verify that this has 6 zeroes in ( 0 , 6 ) .